A High-Performance Isolated SEPIC Converter for Non-Electrolytic LED Lighting - Sulaiha Ahmad; Nadia Mei Lin Tan; M. Zafri Baharuddin; Giampaolo Buticchi (IEEE Access)
This paper proposes a high-performance isolated single-ended primary inductor converter (SEPIC) that is integrated with a non-dissipative snubber for a light-emitting diode (LED) driver. The proposed LED driver employs the snubber circuit to minimize any switching overvoltage caused by parasitic leakage inductance of the high-frequency transformer in the isolated SEPIC converter. This paper also presents a detail theoretical analysis of the proposed LED driver including its operating modes and design calculation. The experimental results of the proposed LED driver at the rated power of 18 W shows that it has a high-power factor, low harmonics, employs non-electrolytic capacitors, low switching stress, high reliability and high efficiency.